An Exploration of Students’ Autonomous Vocabulary Learning through Marvel Cinematic Universe (MCU) Movies - Rohmat Hidayat; Wawan Tarwana; Rina Herlina (Universitas Galuh, 2026)
Vocabulary acquisition is central to language learning, and in recent years, movies have become popular tools for supporting learner independence. The Marvel Cinematic Universe (MCU) offers engaging and authentic content, making it a compelling medium for vocabulary development. While many studies emphasize the value of authentic materials in theory, fewer have examined how students actually experience autonomous vocabulary learning through entertainment media such as MCU films. This study aims to explore senior high school students’ experiences in independently learning English vocabulary through MCU movies, including the strategies they use, challenges they face, and the outcomes they achieve. A qualitative descriptive design was employed. Data were collected through semi-structured interviews with six students, indirect observation via reflective journals, and documentation of students’ vocabulary results. Thematic analysis was used to interpret the data. Students reported high motivation and enjoyment while learning through MCU content. The findings of this research showed that students employed various strategies such as pausing, using subtitles, repeating scenes, and maintaining vocabulary journals. Challenges included fast speech, slang, and distractions from action scenes, which students overcame through self-adjusted learning strategies. Thus, it is concluded that MCU movies are effective and enjoyable tools for supporting autonomous vocabulary learning. They enhance learner motivation, contextual understanding, and promote independent language acquisition.